THE ENERGY CONSUMPTION OF REFRIGERATOR USING CFC 12 AND HFC 134A - Budihardjo Budihardjo (Mesin, 1999)
A market survey found ± 7 companies registered to assemble refrigerators, with annual production capacity 600,000 units (1995) using CFC 12 as a refrigerant. The Association of Indonesia Electric Appliance Manufacturers and Suppliers has decided to convert refrigerant from CFC 12 to HFC 134a by January 1998. The inï¬‚uence of ODS and non ODS substances in refrigerators on energy consumption has been performed. The energy consumption of a manually defrost, single door, 150 Liter typical capacity refrigerators were measured at the Refrigerator Testing Laboratory University of Indonesia based on the protocol of ISO 7371 (E) 1995 under the ambient temperature of 30 "C with relative humidity between 60 % to 75 %.The averaged energy consumption of 7 units CFC-refrigerator were between 1. 1'1 and 1.38 kWh/24h, and for the HFC 134a-refrigerators between 1.03 and 1.22 kWh/24h. The energy consumption differences were approximately between 2 to 16 %.